(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Thiazole is an important nucleus owing to its wide range of medical uses. It contains components that are anti-bacterial, anti-fungal, anti-malarial, anti-cancer, anti-allergic, anti-hypertensive, anti-inflammatory, and anti-psychotic, as well as antioxidant, analgesic, and antimicrobial. The thiazole scaffold has been detected in the more than eighteen FDA-accepted medicines in addition to countless research compounds. A literature review on this themes was undertaken from 2015 to the present. Older publications were not investigated since they had already been peer reviewed.